2005
DOI: 10.1200/jco.2004.00.5686
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Study of Fluorouracil, Leucovorin, and Levamisole in High-Risk Stage II and III Colon Cancer: Final Report of Intergroup 0089

Abstract: The 6- to 8-month regimens of LDLV and HDLV without levamisole used in this trial, rather than the previous standard regimen of 12 months of LEV, have become widely used. INT-0089 has long-term follow-up of the largest clinical trial of patients with high-risk colon cancer, documenting not only the durability of the treatment effects, but also the natural history of patients with high-risk colon cancer, and analyses of treatment based on age, race, and comorbid conditions such as obesity, diabetes, and second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
180
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(189 citation statements)
references
References 31 publications
4
180
1
4
Order By: Relevance
“…No difference was observed in the efficacies of 6-and 12-month chemotherapy durations in a 5-fluorouracil (5-FU)/ levamisole adjuvant chemotherapy study [13]. In addition, no difference was found between 6-and 9-month chemotherapy durations in the GERCOR C96.1 trial [14].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…No difference was observed in the efficacies of 6-and 12-month chemotherapy durations in a 5-fluorouracil (5-FU)/ levamisole adjuvant chemotherapy study [13]. In addition, no difference was found between 6-and 9-month chemotherapy durations in the GERCOR C96.1 trial [14].…”
Section: Introductionmentioning
confidence: 88%
“…Moertel et al reported that 12 months of adjuvant chemotherapy with 5-FU plus levamisole yielded excellent outcomes [29]. Thereafter, the Intergroup trial 0089 (INT-0089) and the Groupe Cooperateur Multidisciplinaire en Oncologie trial found no difference in efficacy among 6, 9, and 12 months of 5-FU/LV [13,14]. The ideal duration for adjuvant chemotherapy in patients with colon cancer is 6 months, which is 12 cycles of FOLFOX and 6 of FL.…”
Section: Discussionmentioning
confidence: 99%
“…17 FU and LV administration has since become standard adjuvant chemotherapy for stage III and high-risk stage II CRC. 18,19 Adjuvant chemotherapy is promising for CRC that is highly suspicious for metastasis after curative surgical resection. Furthermore, new active agents such as irinotecan, oxaliplatin, cetuximab, and bevacizumab, have been reported in use for distant-metastatic CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative adjuvant chemotherapy for colon cancer is one of the most important clinical advances in oncology to have been introduced in recent years (21)(22)(23). Prior to 2000, 5-FU was the only useful cytotoxic agent in the adjuvant setting for patients with stage III colon cancer (24).…”
Section: Introductionmentioning
confidence: 99%
“…Haller et al (23) assessed the three chemotherapy regimens: Low-dose leucovorin plus 5-FU regimen; high-dose LV plus 5-FU regimen; and low-dose LV plus levamisole plus 5-FU regimen, each administered for 30-32 weeks. The control arm was levamisole plus 5-FU for 1 year.…”
Section: Introductionmentioning
confidence: 99%